Assessing the Efficacy and Social Validity of CriaTivo, a Curriculum-Based Intervention to Promote Self-Regulation of Writing in Portuguese Elementary Education. (August 2022) - Margarida Veiga-Simão, Ana; Oliveira, Sofia; Silva-Moreira, Janete; Itália Temudo, Maria
Writing has a leading role in learning and, although elementary-school curricula emphasize the development of this complex skill, many students still struggle with their writing performance. This study aimed to assess the efficacy and social validity of CriaTivo, a curriculum-based intervention developed following a Response to Intervention model to promote self-regulation of the writing process (i.e., planning, monitoring, revising) applied to the written composition of narrative texts across third and fourth grades. Two hundred eighty-one Portuguese students (55% boys, M  = 8.58 years, SD  = 0.79) and their teachers participated in the study. A mixed-methods research design was used, and data was collected at two points in time. Regarding the intervention's efficacy, results were promising, depicting improvements at posttest in students' planning and monitoring skills, as also in their writing quality. The findings also supported the intervention's social validity for both students and teachers. Despite requiring further research, CriaTivo appears to be a promising curriculum-based intervention which responds to the previously identified research and practice needs.